Can auditory cues influence the visually induced self-motion illusion? - Schulte-Pelkum, J.; Riecke, Bernhard E.; Caniard, Franck; Bülthoff, Heinrich H. (European Conference on Visual Perception (ECVP), 2005)
It is well known that a moving visual stimulus covering a large part of the visual field can induce compelling illusions of self-motion ('vection'). Lackner (1977 Aviation Space and Environmental Medicine 48 129 - 131) showed that sound sources rotating around a blindfolded person can also induce vection. In the current study, we investigated visuo-auditory interactions for circular vection by testing whether adding an acoustic landmark that moves together with the visual stimulus enhances vection. Twenty observers viewed a photorealistic scene of a market place that was projected onto a curved projection screen (FOV 54 deg × 40 deg). In each trial, the visual scene rotated at 30° s-1 around the Earth's vertical axis. Three conditions were randomised in a within-subjects design: no-sound, mono-sound, and spatialised-sound (moving together with the visual scene) played through headphones using a generic head-related transfer function (HRTF). We used sounds of flowing water, which matched the visual depiction of a fountain that was visible in the market scene. Participants indicated vection onset by deflecting the joystick in the direction of perceived self-motion. The convincingness of the illusion was rated on an 11-point scale (0 - 100%). Only the spatialised-sound that moved according to the visual stimulus increased vection significantly: convincingness ratings increased from 60.2% for mono-sound to 69.6% for spatialised-sound (t19 = -2.84, p = 0.01), and the latency from vection onset until saturated vection decreased from 12.5 s for mono-sound to 11.1 s for spatialised-sound (t19 = 2.69, p = 0.015). In addition, presence ratings assessed by the IPQ presence questionnaire were slightly but significantly increased. Average vection onset times, however, were not affected by the auditory stimuli. We conclude that spatialised-sound that moves concordantly with a matching visual stimulus can enhance vection. The effect size was, however, rather small (15%). In a control experiment, we will investigate whether this might be explained by a ceiling effect, since visually induced vection was already quite strong. These results have important implications for our understanding of multi-modal cue integration during self-motion. [Supported by the EU-funded POEMS Project (Perceptually Oriented Ego-Motion Simulation, IST-2001-39223).]
Keywords: Riecke; Riecke_2005; bernhard-riecke; iSpaceWeb; multi-modal vection; talkWithoutPaper; vection